Resepsi Makna Hijrah di Kalangan Milenial pada Perguruan Tinggi di Sulawesi Barat - Makmur; Anwar Sewang (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2022)
This article seeks to describe and analyze how the reception patterns of the millennial generation at universities in West Sulawesi about hijra and its implications for their lives. The objects of this study include students from STAIN Majene, West Sulawesi University, and IAI DDI Polewali. By using the model of living hadith studies, this paper argues that the model of exegetical reception of the meaning of hijra of the millennial generation at universities in West Sulawesi is based on narratives, namely the hadith text and texts outside the hadith. The meaning of hijra outside the context of the hadith interpreted by the millennial generation is hijra in the context of dressing, hijra in the context of social media, hijra in the context of entertainment, hijra in the context of tradition, hijra in the context of dating and hijra in the context of usury. In addition, it was also found that millennials at universities in West Sulawesi who have made hijra feel more confident, feel more motivated to worship and study Islam, and tend to claim to be the most correct.